Fixed points via a generalized local commutativity - Gerald F. Jungck (International Journal of Mathematics and Mathematical Sciences)
Let g:X→X. The concept of a semigroup of maps which is nearly commutative at g is introduced. We thereby obtain new fixed point theorems for functions with bounded orbit(s) which generalize a recent theorem by Huang and Hong, and results by Jachymski, Jungck, Ohta, and Nikaido, Rhoades and Watson, and others.